2015
DOI: 10.3168/jds.2014-9135
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Efficacy of copper sulfate hoof baths against digital dermatitis—Where is the evidence?

Abstract: Digital dermatitis is a major problem in modern dairy production because of decreased animal welfare and financial losses. Individual cow treatments are often seen as too time consuming by farmers, and walk-through hoof baths have therefore been used extensively to control digital dermatitis. For decades, copper sulfate hoof baths have been used to treat and prevent digital dermatitis. Copper sulfate has been referred to as the industry gold standard when it comes to hoof-bath chemicals. In several scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(58 reference statements)
0
7
0
2
Order By: Relevance
“…Hoof bathing was pointed out as a factor reducing the odds of DD previously (Rodriguez-Lainz et al, 1999); likewise, DD treponemes are mainly isolated from hoof lesions (Evans et al, 2012;Klitgaard et al, 2014;Zinicola et al, 2015). An evaluation of hoof bathing strategies was beyond the scope of this study; however, this should be further investigated, as many treatment regimens failed or were based on clinical trials without control groups (Laven and Logue, 2006;Thomsen et al, 2008b;Thomsen, 2015). Furthermore, chemicals commonly used (e.g., copper sulfate, formalin, glutaraldehyde, and acids) have undesirable side effects, such as irritation to both humans and cows when applied, environmental contamination, and carcinogenic effects (Laven and Logue, 2006;Relun et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoof bathing was pointed out as a factor reducing the odds of DD previously (Rodriguez-Lainz et al, 1999); likewise, DD treponemes are mainly isolated from hoof lesions (Evans et al, 2012;Klitgaard et al, 2014;Zinicola et al, 2015). An evaluation of hoof bathing strategies was beyond the scope of this study; however, this should be further investigated, as many treatment regimens failed or were based on clinical trials without control groups (Laven and Logue, 2006;Thomsen et al, 2008b;Thomsen, 2015). Furthermore, chemicals commonly used (e.g., copper sulfate, formalin, glutaraldehyde, and acids) have undesirable side effects, such as irritation to both humans and cows when applied, environmental contamination, and carcinogenic effects (Laven and Logue, 2006;Relun et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Preventive and curative measures against DD involve antibiotics and other chemicals applied in hoof baths or topically that are not entirely successful (Laven and Logue, 2006;Thomsen et al, 2008b;Berry et al, 2012;Döpfer et al, 2012;Thomsen, 2015). These strategies may cause environmental contamination and expenses associated with treatments and extra labor (Laven and Logue, 2006;Relun et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…However, Laven and Hunt (2002) [ 8 ] reported that hoof bathing daily for seven days with 5% formalin and 10% CuSO4 was effective in controlling DD [ 8 ]. Although it appears that CuSO4 is effective, most published studies do not include a negative control group [ 42 ]. Here we have identified a higher normalized abundance in the expression of genes associated with resistance to antibiotic and toxic compounds in ADD and IDD, namely copper and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…However, formaldehyde is carcinogenic and CuSO 4 is toxic for the environment via accumulation in the soil (Ippolito et al, 2010). Moreover, a recent systematic review revealed that the effectiveness of CuSO 4 footbaths against DD is not adequately supported by the evidence (Thomsen, 2015). In addition, new evidence suggests possible genetic resistance to copper and zinc in microbiomes associated with DD lesions (Zinicola et al, 2015).…”
Section: Effectiveness Of Collective Treatments In the Prevention Andmentioning
confidence: 99%